The Role of Nurses and Midwives in Handling Malnutrition among Pregnant Women and Children: a Scoping Review - Ermiati, Ermiati; Ardianti, Aulia Sabriska; Azizatunnisa, Auliyah Zahra; Sihemran, Kast Kijay (Universitas Padjadjaran, 2024)
The incidence of under-five children suffering from malnutrition in Indonesia continues to rise. Nurses and midwives play a crucial role in providing appropriate interventions to prevent and manage malnutrition. Objective: This scoping review aims to identify and analyze the role of nurses and midwives in the management of malnutrition in pregnant women and children. Methods: The descriptive scoping literature review was conducted using databases such as Google Scholar, PubMed, ScienceDirect, Scopus, and ResearchGate, focusing on studies from the last five years based on inclusion criteria. Article selection were enforced following the PRISMA-ScR pathway. Results: Six articles highlight the roles of nurses and midwives in managing malnutrition in pregnant women and children. Nurses focus on monitoring nutritional status, health education, and medical interventions, while midwives emphasize nutritional monitoring during pregnancy, emotional support, and education. Discussion: Nurses and midwives collaborate in managing malnutrition, requiring proper training and intervention strategies for effective care. Conclusion: The roles of nurses and midwives in the management of malnutrition in pregnant women both play complementary functions in preventing and addressing malnutrition through a coordinated and holistic approach. Suggestion: Further research is needed on nurse-midwife collaboration to reduce malnutrition and stunting.Keywords: Collaboration; Malnutrition; Midwife; Nurse; Stunting.